Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This question is from this following derivation from pages 204-205 of PDE Evans, 2nd edition. This is from the same proof of Example 9 on those pages of the textbook, and I asked a question about that as well (see Compact support).

Now $n=2k+1$ and $\alpha(n) = \frac{\pi^{n/2}}{\Gamma(\frac n2+1)} = \frac{\pi^{k+\frac 12}}{\Gamma(\frac n2+1)}$. Since $\Gamma\left(\frac 12\right)=\pi^{1/2}$ and $\Gamma(x+1)=x\Gamma(x)$ for $x > 0$, we can compute $$\frac{n \alpha(n)}{\pi^k 2^{k+1}}=\frac{n\pi^{1/2}}{2^{k+1}\Gamma(\frac n2+1)}\color{blue}{=\frac{1}{(n-2)(n-4)\cdots5\cdot3}=\frac{1}{\gamma_n}}$$

May I ask how were the last two equalities obtained (highlighted in $\color{blue}{\textbf{blue}}$)? All I know so far was that the first equality is due to plugging in the expression of $\alpha(n) = \frac{\pi^{k+\frac 12}}{\Gamma(\frac n2+1)}$.

share|improve this question
add comment

1 Answer 1

up vote 4 down vote accepted

The functional equation $\Gamma(x+1) = x\Gamma(x)$ yields

$$\begin{align} \Gamma\left(\tfrac{n}{2}+1\right) &= \Gamma\left(\tfrac{n}{2}\right)\tfrac{n}{2}\\ &= \Gamma\left(\tfrac{n}{2}-1\right)\tfrac{n}{2}\tfrac{n-2}{2}\\ &= \Gamma\left(\tfrac{n}{2}-r\right)\prod_{m=0}^r\tfrac{n-2m}{2} \\ &= \Gamma\left(\tfrac{1}{2}\right)\cdot\prod_{m=0}^{k}\left(\tfrac{n}{2}-m\right)\\ &= \pi^{1/2}\prod_{m=0}^k\frac{n-2m}{2}\\ &= \frac{n\pi^{1/2}}{2^{k+1}}\prod_{m=1}^k(n-2m). \end{align}$$

Plug that in, and you have the first of the equalities. For the second, the definition of $\gamma_n$ would probably be helpful.

share|improve this answer
    
Yeah, that second inequality turns out to just be a definition by the textbook author. From page 79 (in section 2.4, Wave Equation - solution for odd $n$) of PDE Evans, 2nd edition, $$\gamma_n=1\cdot 3 \cdot 5 \cdots(n-2).$$ –  glace Jul 3 at 21:15
    
Just apply the functional equation repeatedly, $$\Gamma\left(\tfrac{n}{2}+1\right) = \tfrac{n}{2}\Gamma\left(\tfrac{n}{2}\right) = \tfrac{n}{2}\tfrac{n-2}{2}\Gamma\left(\tfrac{n}{2}-1\right) = \tfrac{n}{2}\tfrac{n-2}{2}\tfrac{n-4}{2}\Gamma\left(\tfrac{n}{2}-2\right)$$ etc. –  Daniel Fischer Jul 3 at 21:54
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.